Estimating and analyzing energy efficiency in German and Colombian manufacturing industries using dea and data panel analysis. Part I: Energy-intensive sectors (2015)
In this article, data envelopment analysis (DEA) is employed to study the comparative performance of German and Colombian energy-intensive sectors between 1998 and 2005. The results of the DEA indicate that the great majority of energy-intensive sectors improved on this index during the sample period, demonstrating that energy input is an important variable within the production structure and a key element in technology development. At a second stage, regression analysis using panel data analysis reveals that several factors, including labor productivity, the share of electricity, investments and enterprise size can be considered determinants of differences in energy efficiency among German and Colombian energy-intensive sectors. Our results also show that different energy policies should apply, and that they should encourage the importance of energy efficiency in order to achieve a sustainable economic development and climate stabilization today and in the near future.